2015
DOI: 10.1590/1413-785220152306148750
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck non-union treatment by valgus intertrochanteric osteotomy

Abstract: OBJECTIVE: The purpose of this study was to evaluate the performance of valgus intertrochanteric osteotomy in femoral neck non-union.METHODS: Forty-two patients with femoral neck fractures with non-union treated using Pauwels' intertrochanteric osteotomy were reviewed. Demographics, time elapsed between fracture and surgery, follow--up, osteosynthesis used, Garden's classification, limb shortening, and x-rays were evaluated. RESULTS: Twenty-two men and 20 women were reviewed. The youngest patient was 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Before the osteotomy, limb length discrepancy was present in 24 patients. Valgus osteotomy led to the equalization in 16 patients [7]. In the current study, the success rate of valgus osteotomy was measured as 90%.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Before the osteotomy, limb length discrepancy was present in 24 patients. Valgus osteotomy led to the equalization in 16 patients [7]. In the current study, the success rate of valgus osteotomy was measured as 90%.…”
Section: Discussionmentioning
confidence: 61%
“…However, the rate of hip replacement is associated with the followup duration. This is because degenerative changes progress with time and total hip replacement could become necessary [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartsmann et al 3 reported good outcome treating femoral neck non-union with valgus osteotomy. They have stated their preference of DHS over angle blade plate given DHS provides rigid stability, is less aggressive, easier to perform, and allows compression over non-union site.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contraindications to valgus osteotomy such as osteonecrosis with incongruence, poor bone quality and reabsorption. However, radiographic evidence of osteonecrosis alone without collapse is not a contraindication 3 .…”
Section: Discussionmentioning
confidence: 99%